Hodnocení finanční situace podniku a návrhy na její zlepšení - Synek, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Cílem této bakalářské práce je zhodnocení ekonomického vývoje a návrh řešení na zlepšení finanční situace společnosti Mürdter Dvořák, lisovna, spol. s.r.o. v letech 2018-2021. Práce je strukturována do čtyř hlavních kapitol. První kapitola je zaměřena na teoretická východiska finanční analýzy, která jsou nezbytná pro pochopení dané problematiky. Druhá kapitola implementuje tyto poznatky do praxe a je zanalyzován skutečný stav podniku. Třetí kapitola shrne výsledky, klady a zápory a poslední kapitola představí návrh na zlepšení finanční situace společnosti.

The aim of this bachelor’s thesis is an evaluation of the economic development and proposal of improved financial situation of the company Mürdter Dvořák, lisovna, spol. s.r.o. for the years 2018 to 2021. Thesis is divided into four main chapters. First chapter is focused on explaining the necessary theoretical background of financial analysis needed to understand this topic. Second chapter implements these methods into practice and analyzes the current financial state of the company. The third chapter summarizes the results, pros and cons and the last chapter presents a proposal for improving the financial situation of the company.
Evaluation of the Financial Situation of a Company and Proposals to its Improvement
Keywords: finanční analýza; rozvaha; výkaz zisku a ztrát; ukazatele finanční analýzy; likvidita; financial analysis; balance sheet; profit and loss statement; indicators of financial analysis; liquidity